Perancangan Dan Implementasi Sistem Antropometri Bayi Berbasis ESP32-S3: Integrasi Sensor Suhu dan Pencatatan Data IoT Pada Google Spreadsheet - Alief Fadhillah; Dewi Laksmiati; Zainul Mufid (Jurnal Ilmiah Giga, 2026)
Routine anthropometric monitoring is standard practice for early detection of growth disorders in infants, and is complemented in this study by body temperature monitoring as a fever indicator. Conventional approaches using separate instruments for weight, body length, and body temperature are time-consuming and susceptible to transcription errors, particularly in high-volume posyandu settings. This study developed an integrated infant anthropometric measurement device based on the ESP32-S3 microcontroller, combining a 20 kg load cell with an HX711 amplifier for weight, an HC-SR04 ultrasonic sensor for body length, and a DS18B20 sensor for axillary temperature. Measurement data are entered via USB keyboard, shown on an LCD, and automatically transmitted to Google Spreadsheet via HTTP GET to Google Apps Script. The device computes weight-for-age, length-for-age, and BMI-for-age z-scores per Ministry of Health Regulation No. 2 of 2020. Accuracy testing over 100, 90, and 10 trials for weight, length, and temperature yielded a 93% accuracy rate within ±0.1 kg, length accuracy ≥90% at every point across 0–80 cm (90 trials total), and a maximum temperature deviation of 0.1°C. Integrated testing on two healthy infants aged 2 and 12 months produced results consistent with WHO reference medians, with cloud transmission completed within 1–2 seconds per session.